<h3>
Answer: Yes they are equivalent</h3>
==============================================
Work Shown:
Expand out the first expression to get
(a-3)(2a^2 + 3a + 3)
a(2a^2 + 3a + 3) - 3(2a^2 + 3a + 3)
2a^3 + 3a^2 + 3a - 6a^2 - 9a - 9
2a^3 + (3a^2-6a^2) + (3a-9a) - 9
2a^3 - 3a^2 - 6a - 9
Divide every term by 2 so we can pull out a 2 through the distributive property
2a^3 - 3a^2 - 6a - 9 = 2(a^3 - 1.5a^2 - 3a - 4.5)
This shows that (a-3)(2a^2 + 3a + 3) is equivalent to 2(a^3 - 1.5a^2 - 3a - 4.5)
That would a set of 5 numbers in ascending order with 4 being the middle one and the other 4 being the highest possible So it is
2, 3, 4, 9, 10
Mean is 28/5 = 5.6 answer
( I am assuming that each number is different)
Of duplicates is allowed then its 4 4 4 10 10 whose mean is 6.4
Answer:
102 is the correct answet
Answer:
AB is congruent is CD. (Last one)
Step-by-step explanation:
Hypotenuse leg is when the hypotenuse and ONE (you only need one, not two) leg of the triangle are congruent in a RIGHT triangle.
In the image, you already know that it is a right triangle and you know that the hypotenuse are congruent (Reflexive Prop) .You just need to know that the legs are congruent. So you choose which one has the legs congruent. The leg pairs that can be congruent are AD and CB or DC and AB. The only one that matches this is the last one
Those are all the answers hope this helps.